#TITLE_ALTERNATIVE# - AKHMAD NURSYAMSY FAHRURRYZA (NIM : 13707060); Pembimbing : Dr.Ir.Aditianto Ramelan
Cement is one of the main material used to manufacture concrete building construction, there is a high demand of the usage of cement for this purposes. Hence the production of cement in the industry increased. However, there are complaints from the building construction industry on different hydrated cement product quality. Quality of hydrated cement product can be determined by the compressive strength analysis and hydrated cement phase involved. Two pure different cements namely B and C were used and made into paste with water addition. The hydrated cement product were then characterize by its compressive strength and its phases formed by using X-ray diffraction. The paste were made of w/c 0.3, 0.4, and 0.5 and cured for 3, 14, and 28 days. X-Ray Diffraction characterisation were carried out for sample with w/c ratio of 0.3 with curing time 3 and 28 days for cement B and C to determine the hydrated cement phases formed in the samples. It is observed that the compressive strength value of cement B (w/c = 0.3) curing time 3 days is 9.5 MPa, cement C (w/c= 0.3) is 48.3 MPa. After 28 days, the compressive strength of cement B (w/c=0.3) is 29 MPa, while cement C (w/c = 0.3) is 41.6 MPa. At 3 days, cement B produced hydrated cement phase is Calcium Silicate Hydrate is 22.7 w/o, while the cement C produces hydarated cement phase Calcium Silicate Hydrate 20.2 w/o and Calcium Hydroxide 24.5w/o. The curing time of 28 days, cement B is producing hydrated cement phase calcium silicate hydrate 26 w/o, while cement C is producing Calcium Silicate Hydrate 25.1w/o, and Calcium Hydroxide 23.1w/o and Ettringite 6 w/o. The mixing process of cement and water is very important and determined the quality of Hydrated Cement Product. Hydrated cement phase Calcium Silicate Hydrate and Calcium Hydroxide increased the strength, whereas hydrated cement phase Ettringite decreased it. The phases formed determined the mechanical properties of hydrated cement product. Further research regarding the accurate determination of hydrated cement product quality need to be deepen.